2022
DOI: 10.3390/en15228578
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Data-Driven Optimization for Maximizing the Photovoltaic Power with Tilt Angle Adjustment

Abstract: This paper reports on how the trade-off between the incident solar irradiance and conversion efficiency of a photovoltaic panel affects its power production. A neural network was developed through statistical analysis and a data-driven approach to accurately calculate the photovoltaic panel’s power output. Although the incident beam irradiance at a specified location directly relates to the tilt angle, the diffusion irradiance and energy conversion efficiency are nonlinearly dependent on a number of operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The study found that a tilt angle of 15 degrees and a 4-foot interrow spacing were the most efficient, as they provided the highest total collector irradiance, performance ratio, and annual energy output. Ye et al (2022) developed a novel approach to optimize the energy output of solar farms based on data analysis. The approach focuses on powerbased optimization and has been proven to yield different tilt angles compared to conventional irradiance-based optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that a tilt angle of 15 degrees and a 4-foot interrow spacing were the most efficient, as they provided the highest total collector irradiance, performance ratio, and annual energy output. Ye et al (2022) developed a novel approach to optimize the energy output of solar farms based on data analysis. The approach focuses on powerbased optimization and has been proven to yield different tilt angles compared to conventional irradiance-based optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Для повышения энергоэффективности ФЭС применяют следующие способы: регулируют угол наклона фотоэлектрических ФЭМ в зависимости от времени года, что обеспечивает прирост генерации на 9,7 % ежегодно, 12,74 % ежемесячно, 24,78 % ежечасно относительно горизонтально установленных ФЭМ [7]. Приведены данные исследований, проведенных в Канаде, которая географически расположена примерно на одних и тех же широтах, что и Российская Федерация; -применяют двухсторонние ФЭМ, которые в среднем во всем мире способствуют повышению генерации электроэнергии на величину от 10 % (при альбедо 0,25 -типично для естественного почвенного покрова) до 20 % (при увеличении альбедо грунта до 0,5) в сравнении со стационарными односторонними ФЭМ [8];…”
unclassified